2017
DOI: 10.20524/aog.2017.0122
|View full text |Cite
|
Sign up to set email alerts
|

Fecal occult blood testing for the prediction of small-bowel pathology detected by capsule endoscopy: a systematic review and meta-analysis

Abstract: BackgroundFecal occult blood testing (FOBT) has been suggested as a potential screening tool for small-bowel capsule endoscopy (CE). We conducted a meta-analysis of studies correlating FOBT and CE findings to examine the predictive value of positive FOBT for CE findings.MethodsPubMed and Embase search. Sensitivity, specificity and diagnostic odds ratios (DORs) were calculated.ResultsSix studies were identified. Four used fecal immunochemical testing (FIT), one used FIT and guaiac FOBT, one used hemoglobin/hapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…FIT has been proven to be useful in detecting colorectal pathology, however a significant proportion of false positives raises the possibility that it may also be useful in detection of small bowel lesions 13 . There is limited data on this topic, however a recent meta-analysis of six publications suggested FIT is not a good predictor of findings on SBCE 15 . In the meta-analysis, sensitivity and specificity of FIT in prediction of SB pathology were 0.48 and 0.60 respectively, both considerably lower than our trial (0.69 and 0.89 at > 45 ug Hb/g).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FIT has been proven to be useful in detecting colorectal pathology, however a significant proportion of false positives raises the possibility that it may also be useful in detection of small bowel lesions 13 . There is limited data on this topic, however a recent meta-analysis of six publications suggested FIT is not a good predictor of findings on SBCE 15 . In the meta-analysis, sensitivity and specificity of FIT in prediction of SB pathology were 0.48 and 0.60 respectively, both considerably lower than our trial (0.69 and 0.89 at > 45 ug Hb/g).…”
Section: Discussionmentioning
confidence: 99%
“…The studies included differed significantly from our trial, which may have contributed to this discrepancy. First, there were significant delays between analysis of FIT and completion of SBCE, in some cases up to 4 months 15 . In the meta-analysis, time between FIT to SBCE ranged between 3 days to 4 months, with an average lag of 1 to 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These tests are based on the concept of detecting blood or shredded cell debris from vascularized polyps, adenomas and cancers. Owing to their simplicity and user-friendliness, gFOBT and FIT have found widespread use in CRC screening but are burdened by low sensitivity and specificity [ 5 ]. Invasive tests include flexible sigmoidoscopy and colonoscopy, have higher sensitivity and specificity because they offer direct visualization and pathology specimen collection [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fecal immunochemical test (FIT) is used widely in colorectal cancer screening. A 2017 small systematic review showed a low sensitivity and specificity of FIT for significant findings on CE where FIT used as a selection tool for SBCE showed a sensitivity of 0.48 and a specificity of 0.60; i.e., neither a positive nor a negative FIT were good predictors of SB findings on CE [12]. However, more recent data provided by our colleagues have suggested FIT to be a useful biomarker in predicting the likelihood of small bowel pathology in patients with anemia.…”
Section: Biomarkersmentioning
confidence: 99%